2020
DOI: 10.1590/0103-8478cr20190996
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of monensin poisoning in cattle due to supplementation error

Abstract: Iatrogenic intoxications occur in domestic animals. Mortality was observed in a group of calves, reaching 20 deaths until the day of the technical visit, with or without sudden clinical signs, on a farm in the city of Pires do Rio, State of Goiás, Brazil. Deaths after the visit were not accounted systematically. Clinical signs included muscle weakness, ataxia, recumbency, bilateral jugular distention, and death. Suspected diagnosis of poisoning by ionophore antibiotics was made based on clinical and laboratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
2
3
0
1
Order By: Relevance
“…Monensin poisoning caused degenerative and necrotic changes in the myocardium and skeletal muscles in buffaloes in this study, similar to those reported in other studies with buffaloes (Rozza et al 2006, 2007, Bence et al 2018, Garcia et al 2020) and, cattle (Gava et al 1997, Brito et al 2020, horses (Pavarini et al 2011) and, sheep (Souza et al 2008, given that only in the latter species, cardiac fibrosis has already been described (França et al 2009).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Monensin poisoning caused degenerative and necrotic changes in the myocardium and skeletal muscles in buffaloes in this study, similar to those reported in other studies with buffaloes (Rozza et al 2006, 2007, Bence et al 2018, Garcia et al 2020) and, cattle (Gava et al 1997, Brito et al 2020, horses (Pavarini et al 2011) and, sheep (Souza et al 2008, given that only in the latter species, cardiac fibrosis has already been described (França et al 2009).…”
Section: Discussionsupporting
confidence: 91%
“…As for the lesion pattern in other species, Barros (2007) also highlighted that cattle and horses tend to have more marked lesions in the heart. However, this trend was not observed in later outbreaks of monensin poisoning in these species (Pavarini et al 2011, Sousa et al 2019, Brito et al 2020.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Researchers noticed that monensin inhibited the growth of Danio rerio and Daphnia magna . When accidentally ingested monensin over dosage in mammals, such as cattle or pigs, muscle weakness, ataxia, and even death could occur . Similarly, in this work, acute toxicity results showed that monensin had strong toxicity to earthworms.…”
Section: Resultssupporting
confidence: 56%
“…• A consequence of faults in the calculation of doses • Excessive ingestion of ionophores because of inappropriate mixing of the drug with the feed [6] • Administration of ionophores to more susceptible species [7] • The use of ionophores in combination with other drugs enhances their effects [8]. Hence, antioxidant supplementation may mitigate salinomycin-induced toxicity.…”
Section: Introductionmentioning
confidence: 99%